Morphological features and new description of the fossil species Thalassiosira dolmatovae (Bacillariophyceae) - Gladenkov, Andrey (Phytotaxa, 2013)
Specimens of the Neogene marine diatom Thalassiosira dolmatovae have been studied with a scanning electron microscope for the first time. The observations revealed the morphological features typical of this species including arrangement of different kinds of processes. T. dolmatovae has one single subcentral strutted process, a ring of marginal strutted processes, a labiate process located at the margin and enclosed by two strutted processes. Marginal strutted processes with outward extensions and without inward extensions have internal openings surrounded by 4 satellite pores. The location of a labiate process not on the valve face and the presence of marginal strutted processes with outward extensions indicate that the studied species really belongs to genus Thalassiosira not to genus Shionodiscus. A valid description of T. dolmatovae is given.